Experimental observation of the Poincaré-Birkhoff scenario in a driven many-body quantum system - Tomkovič, Jiří; Müssel, Wolfgang; Strobel, Helmut; Oberthaler, Markus K. (Physical review, 2017)
Accessing the connection between classical chaos and quantum many-body systems has been a long-standing experimental challenge. Here, we investigate the onset of chaos in periodically driven two-component Bose-Einstein condensates, whose small quantum uncertainties allow for exploring the phase space with high resolution. By analyzing the uncertainties of time-evolved many-body states, we find signatures of elliptic and hyperbolic periodic orbits generated according to the Poincaré-Birkhoff theorem, and the formation of a chaotic region at increasing driving strengths. The employed fluctuation analysis allows for probing the phase-space structure by use of only short-time quantum dynamics.
Gesehen am 28.03.2018